The Effect of Green Investment and Carbon Emission Disclosure on Financial Reporting Quality in Energy Sector Companies Listed on the IDX (2021–2023) (International Journal of Economics and Management Research, 2026)
This study investigates the effect of green investment and carbon emission disclosure on the quality of financial reporting among energy sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The research uses a quantitative approach and secondary data, with an exploratory design aimed at examining causal relationships between the independent variables and financial report quality. Green investment refers to the allocation of capital toward environmentally sustainable initiatives, while carbon emission disclosure involves the transparency of companies in reporting their greenhouse gas emissions. Financial report quality is measured through accrual quality and earnings persistence.Statistical analysis was conducted using panel data regression. The results indicate that neither green investment nor carbon emission disclosure has a statistically significant influence on the quality of financial reports. The significance values obtained were 0.525 for green investment and 0.069 for carbon emission disclosure, both above the 0.05 threshold. These findings suggest that while environmental responsibility practices are increasing in visibility, they have not yet translated into improvements in financial reporting quality in the energy sector. External pressures or compliance motives may drive environmental disclosures, rather than a commitment to improving transparency or financial integrity.The study highlights the necessity for further investigation into the mechanisms by which sustainability practices can enhance financial reporting. It also suggests that regulatory enforcement alone may not be sufficient to influence reporting behavior in the short term. Keywords: green investment, carbon emission disclosure, financial reporting quality, energy sector, sustainability reporting